2018
DOI: 10.1080/15504263.2018.1531185
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Drinking Motives Among Suddenly Bereaved College Students

Abstract: Objective: Thousands of Americans grieve the sudden death of a loved one each year. These sudden deaths may be the result of violent deaths, as in the cases of homicide, suicide, or fatal accidents, or may occur as the result of natural causes such as heart attacks or strokes. Sudden loss survivors often experience negative mental health outcomes such as depression, prolonged grief disorder, and posttraumatic stress disorder. Survivors may also misuse alcohol for varied reasons after these losses, which can pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Feelings of grief and mental health distress played a significant role in the increased use of substances in our sample. Previous research found that young adults, including students, who experience a high level of bereavement-related mental health distress may be more likely to engage in maladaptive coping behaviours, such as substance use, than their peers who experience less grief and mental health distress (Eddinger et al, 2019). It is possible that other students' use also increased after their loved one's death, but they did not attribute this to the death.…”
Section: Discussionmentioning
confidence: 97%
“…Feelings of grief and mental health distress played a significant role in the increased use of substances in our sample. Previous research found that young adults, including students, who experience a high level of bereavement-related mental health distress may be more likely to engage in maladaptive coping behaviours, such as substance use, than their peers who experience less grief and mental health distress (Eddinger et al, 2019). It is possible that other students' use also increased after their loved one's death, but they did not attribute this to the death.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, there is a wide range of correlations between coping-related drinking and alcohol-related variables in the literature. Such variables include number of alcoholic drinks ( r = .21–.42; McCabe et al, 2019; McDevitt-Murphy et al, 2017), frequency of consumption ( r = .21–.67; Cloutier et al, 2018; McDevitt-Murphy et al, 2017), alcohol-related problems ( r = .20–.56; Eddinger et al, 2019; Stappenbeck et al, 2013), and risky drinking ( r = .34–.64; Marshall-Berenz et al, 2011; Woolman et al, 2015). There is also variation in the size of the indirect effect for coping motives on the association between PTSD and alcohol use.…”
Section: Self-medication Hypothesismentioning
confidence: 99%
“…In addition, students who were grieving and exhibiting severe depression symptoms were more likely to report drinking alcohol to cope and conform (Eddinger et al, 2018). Over 70% of grieving students who reported losing someone in a sudden, violent death drank alcohol in the past 30 days (Eddinger et al, 2018); the national prevalence of past-month alcohol use in college students is 58% (Substance Abuse and Mental Health Services Administration, 2015). Grieving students also reported higher rates of insomnia (22%) compared with non-bereaved students (17%; Hardison et al, 2005).…”
Section: Grief Prevalence and Outcomesmentioning
confidence: 99%